Understanding barriers, access, and management of marine mixed-stock fisheries in an era of reconciliation: Indigenous-led salmon monitoring in British Columbia - Jade R. Steel; William I. Atlas; Natalie C. Ban; Kyle Wilson; Jayda Wilson; William G. Housty; Jonathan W. Moore (Canadian Science Publishing, 2021)
Wild salmon are central to food security, cultural identity, and livelihoods of coastal Indigenous communities. Yet ongoing inequities in governance, declining fish populations, and mixed-stock ocean fisheries may pose challenges for equitable access between Indigenous fishers and other non-Indigenous fishers. We sought to understand current perceptions among Haíłzaqv (Heiltsuk) fishers towards salmon fisheries and their management. We conducted dockside surveys with both Haíłzaqv fishers and sport fishers, and in-depth interviews with Haíłzaqv fishers, community members, and natural resource managers. From these surveys and interviews we quantified satisfaction among both food, social, and ceremonial fishers and visiting recreational fishers with the current salmon fishery and associated social-ecological drivers, and characterized perceptions among Haíłzaqv people of salmon fisheries and management. Second, we synthesized community perceptions of the revitalization of terminal, communally run salmon fisheries within Haíłzaqv territory as a tool for their future salmon management. Finally, we elicited information from Haíłzaqv fishers about the barriers people in their community currently face in accessing salmon fisheries. Our findings suggest that low salmon abundance, increased fishing competition, and high costs associated with participation in marine mixed-stock fisheries currently hinder access and equity for Haíłzaqv fishers. This community-based research can help strengthen local, Indigenous-led management of salmon into the future.